2007
DOI: 10.2337/db06-1545
|View full text |Cite
|
Sign up to set email alerts
|

Limited Capacity of Human Adult Islets Expanded In Vitro to Redifferentiate Into Insulin-Producing β-Cells

Abstract: Limited organ availability is an obstacle to the widespread use of islet transplantation in type 1 diabetic patients. To address this problem, many studies have explored methods for expanding functional human islets in vitro for diabetes cell therapy. We previously showed that islet cells replicate after monolayer formation under the influence of hepatocyte growth factor and selected extracellular matrices. However, under these conditions, senescence and loss of insulin expression occur after >15 doublings. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
38
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 22 publications
8
38
2
Order By: Relevance
“…We suggest that other factors which are essential for normal function are downregulated in the dedifferentiated cells and although our study suggests that increased cell-cell contact may help to promote the re-establishment of such signals, redifferentiation towards an authentic β-cell phenotype was not achieved. Accordingly, Kayali et al, 22 reported that primary β-cells which had dedifferentiated in culture to an intermediate growth-arrest in the SV40 TAg transformed cells, again as we observed.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tsupporting
confidence: 67%
See 1 more Smart Citation
“…We suggest that other factors which are essential for normal function are downregulated in the dedifferentiated cells and although our study suggests that increased cell-cell contact may help to promote the re-establishment of such signals, redifferentiation towards an authentic β-cell phenotype was not achieved. Accordingly, Kayali et al, 22 reported that primary β-cells which had dedifferentiated in culture to an intermediate growth-arrest in the SV40 TAg transformed cells, again as we observed.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tsupporting
confidence: 67%
“…Several lines of evidence suggest that the maintenance of a fully differentiated functional β-cell phenotype is inconsistent with proliferation: primary β-cells withdraw from the cell cycle when undergoing final differentiation, 7 proliferation of primary β-cell in vitro is associated with their dedifferentiation [4][5][6]21,22 and transformed, proliferative β-cell lines exhibit a phenotype typical of dedifferentiated primary β-cells. 3 We have therefore tested the hypothesis that experimentally-induced growth-arrest of transformed β-cell lines will improve their function by driving their differentiation towards the original β-cell phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, positivity for Ki67 of cells expressing Ipf-1 would suggest that cells of epithelial origin can proliferate at least for a given time, as proposed initially by Hayek and co-workers. 31 These authors have recently compared their protocol 4 with that of Gershengorn et al 25 confirming that, although with some differences in terms of number of cells and replication time, which may depend on the culture conditions used, initial proliferation of cells positive for Ipf-1 can be reproducibly observed at early stages of islet culture. However, taking into account the recent results from b-cell lineage tracing experiments, an alternative explanation of our findings is that even if there was an initial transition of b-cells to a mesenchymal phenotype at early times in culture, these cells may die off and be taken over by a population of mesenchymal cells that continue to proliferate and to persist at the later passages of these cultures, as observed in b-cells expressing GFP in mice.…”
Section: Resultsmentioning
confidence: 89%
“…26 However, several groups have recently provided evidence, based on cell-lineage tracing experiments in mouse, that mesenchymal cells from pancreatic islets do not originate by an epithelial-mesenchymal transition from b-cells, but may derive from a population of pre-existing connective tissue mesenchymal cells associated with pancreatic epithelial structures. [27][28][29][30][31] Here, we report results from experiments aimed at the characterization of human pancreatic islet-derived mesenchymal (hPIDM) cells. These results provide clear evidence that, in the presence of fetal bovine serum (FBS), cultures of purified adult human pancreatic islets can generate an intermediate mixed cell population from which mesenchymal cells positive for nestin can be reproducibly obtained.…”
mentioning
confidence: 99%
“…34 However, loss of β cell phenotype including diminished insulin expression occurs during long-term culture without ECM support. 35,36 In the present study, fibrin culture of human fetal islet-epithelial cell clusters showed only a slight increase in the number of insulin-and glucagon-positive cells compared with controls. The possible reasons for this observation can be explained by the following: (1) the CMRL1066 plus 10% FBS culture medium does not contain enough factors to sufficiently promote the differentiation of human fetal islet-epithelial cell clusters into endocrine cells during 1 and 2 weeks of culture; (2) the pancreatic samples from fetal age of 15-21 weeks display a large number of different cell populations, and (3) immunofluorescence staining may not have sufficient sensitivity for detecting differentiated cells since there was significantly increased mRNA expression of these hormones, as well as a significant increase in PDX-1 protein expression in fibrincultured cells compared with controls.…”
Section: Discussionmentioning
confidence: 86%